Homme sauvage et femmes étrangères, (III), la reine étrangère et l'homme prophétique - féminisme, genre et post-colonialisme: le cycle d'Élie (1 R 17 - 2 R 2) en perspectives de "genre"/gender - Wacker, Marie-Theres (Lectio difficilior, 2019)
Building on a former contribution (lectio 2/2014) on the Elijah cycle (1 Kings 17 –2 Kings 2) read with different approaches of a gender-sensitive exegesis, this article explores how postcolonial approaches change or sharpen an analysis of the Elijah story, especially relating to 1 Kings 21. Following a short introduction to the most well-known foundersof postcolonial theory (Fanon, Said, Bhabha, Spivak) and some reflections on the reception of postcolonial studies in biblical studies/OT studies, a first reading of 1 Kings 21 focusses on land grabbing, whereas a second reading concentrates on the figureof Jezebel and analyses 1 Kings 21 within the context of 1 Kings 16,29-34 –2 Kings 2,14. The present contribution is an expanded version of the third lecture delivered as a visiting professor at the École Pratique des Hautes Études in Paris (spring 2014).